Differentiation of flea communities infesting small mammals across selected habitats of the Baltic coast, central lowlands, and southern mountains of Poland - Kowalski, Krzysztof (Parasitol Res, 2014)
Only a few studies comparing flea composition on the coast and in the mountains have been conducted. We investigated differences in flea communities infesting small mammals in selected habitats in northern, central, and southern Poland. We predicted (1) a greater number of flea species in the southeastern Poland and a lower number in the north, (2) a greater number of flea species in fertile and wet habitats than in poor and arid habitats, and (3) a low similarity of flea species between flea communities in western and eastern Poland. We found a negative effect of increasing latitude on flea species richness. We suppose that the mountains providing a variety of environments and the limits of the geographic ranges of several flea subspecies in southeastern Poland result in a higher number of flea species. There was a positive effect of increasing wetness of habitat on flea species richness. We found a high diversity in flea species composition between western and eastern Poland (beta diversity = 11) and between central and eastern Poland (beta diversity = 12). Re-colonization of Poland by small mammals and their ectoparasites from different (western and eastern) refugees can affect on this high diversity of flea species.